Compensation of Low Current by Photoelectric Methods (The International Journal for Scientific Research, 2023)
The cost of extracting conventional energy is increasing and conventional energy itself is becoming very scarce and research indicates an increase in pollution, and it also shows that the depletion of conventional energy sources is inevitable. All that means there is a dire need for an alternative type of energy, that is clean, easy to install and cost effective and that is Photovoltaic (PV) energy, which is available in abundance in the study area of research, in which unreliable conventional energy is used, is usually out of power for more than 12 hours a day and this shortage in power affects many sectors in the city, such as hospitals, schools, farms and basic facilities and even the refrigerators of the dead, whose bodies have been decomposed due to power shortage.This paper studies the power situation in the town area, on latitude (31.53) and longitude (23.54), and finds an alternative renewable energy source, namely PV, and designs a reliable PV system that would compensate for the usual conventional power shortage suffered by Tobruk City. Two load scenarios are considered, one is the required load in which only the essential electric devices are involved and the other is optional in which some extra electric households are added. It is believed that this power solution would not only guarantee the availability of power for the town area, but it also saves money in the long run and saves the environment since it is a clean that is easy to install and maintain.
Keywords: Photo Voltaic; PV; Renewable Energy